Improving Comprehension of State Administrative Law Among Administrative Officials of Kelurahan Limba U II in Public Service Provision - Sri Nurnaningsih Rachman; Melki T. Tunggati (Carmin: Journal of Community Service, 2026)
This community service activity aims to measure the level of understanding of the apparatus of the Limba U II Urban Village Office, Gorontalo City, regarding the principles of State Administrative Law in the provision of public services, and to implement the strengthening of this legal understanding through a participatory action approach to improve the quality of public services in the urban village. The method used in this activity is participatory action, which synergistically integrates three methods: interactive legal counseling, focus group discussion (FGD), and case simulation (role play). The activity was carried out one day on February 26, 2026, and was attended by 15 urban village apparatus consisting of the Urban Village Head, Urban Village Secretary, Section Chiefs, and implementing staff. The level of understanding was measured through pre-test and post-test instruments containing four indicators: basic knowledge of State Administrative Law, general principles of good governance (algemene beginselen van behoorlijk bestuur), authority (bevoegdheid), and discretion (freies Ermessen). The results of the activity showed that the level of understanding of the apparatus before the activity was still relatively low, with an average pre-test score of 48.7 out of a scale of 100. After the implementation of the participatory action approach, the average post-test score increased significantly to 78.4, or an increase of 29.7 points (60.98%). The conclusion of this activity indicates that the participatory action approach proved effective in measurably increasing the understanding of the apparatus regarding the principles of State Administrative Law and encouraging the realization of transparent, accountable, and rule-of-law-based public services at the Limba U II Urban Village Office, Gorontalo City.